Mobilizing mini-publics: the causal impact of deliberation on civic participation using panel data - Boulianne, Shelley; Chen, Kaiping; Kahane, David (My University, 2020)
Deliberative exercises may re-invigorate civic life by building citizens’ capacity to engage in other types of civic activities. This study examines members of a citizens’ panel (n=56) who participated in a six-day deliberative event on climate change and energy transition in Edmonton, Alberta (Canada) in 2012. We compared panelists’ civic engagement, political interest, and political knowledge with those of the general population using a concurrent random digit dialing survey conducted 2.5 years after the event (n=405). Panelists are more likely to talk about politics, and volunteer in the community compared to their counterparts in the larger population. Examining three points in time, we reveal a trajectory of increasing political knowledge and civic engagement. Finally, we examine the mechanisms that mobilize panelists into greater civic engagement. This study illustrates how deliberative events could strengthen engagement in civic and political life, depending on the degree to which deliberation was perceived to have occurred.
Keywords: deliberative democracy; civic engagement; political interest; political knowledge; longitudinal